Advances in Gelatin-Based Tissue Engineering Using HRP/H2O2 - Marino Basha; Ahmad Aburub; Filippos F. Karageorgos; Georgios Tsoulfas; Aleck H. Alexopoulos (Gels)
Gelatin, a biocompatible and biodegradable polymer, has garnered considerable attention in tissue engineering (TE) due to its diverse applications enabled by its tunable physical properties. Among the various strategies employed for the fabrication of gelatin-based hydrogels, the use of horseradish peroxidase (HRP) and hydrogen peroxide (H2O2) as a catalytic system has been highlighted as an effective tool for producing hydrogels with highly modifiable properties. Herein, we explore recent progress in the utilization of the HRP/H2O2 catalytic system for the creation of gelatin-based hydrogels, with an emphasis on TE applications. Particular attention has been given to the interplay between variations in the concentration equilibrium of HRP and H2O2 and the fine-tuning of gel properties tailored for various TE applications. Emerging trends, such as in situ gelation and hybrid bioinks, have also been examined through the lens of their prospective applications, extrapolating from the findings in cell cultures and animal models. A comprehensive review of two databases (Scopus and Web of Science) was conducted. The data extracted from each study included the materials used for each application, methods used for material preparation, cells used in the TE application, laboratory animals used, and whether computational/simulation techniques were implemented. The applications included both homopolymeric hydrogels, using only gelatin as the backbone, and copolymeric hydrogels, with ≥2 polymers.